2017
DOI: 10.1136/bmjopen-2016-013457
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture and PC6 stimulation for the prevention of postoperative nausea and vomiting in patients undergoing elective laparoscopic resection of colorectal cancer: a study protocol for a three-arm randomised pilot trial

Abstract: IntroductionThis study aims to assess the feasibility of acupuncture and a Pericardium 6 (PC6) wristband as an add-on intervention of antiemetic medication for the prevention of postoperative nausea and vomiting (PONV) in patients undergoing elective laparoscopic colorectal cancer resection.Methods and analysisA total of 60 participants who are scheduled to undergo elective laparoscopic resection of colorectal cancer will be recruited. An enhanced recovery after surgery protocol using standardised antiemetic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 19 publications
1
7
1
Order By: Relevance
“…PONV is a frequent complication, and there are a lot of factors influencing it. 14,17 Many studies have shown that drugs such as metoclopramide, dexamethasone, and ondansetron can reduce PONV. Although potency of these drugs is different, they have a limited effect on PONV and they also have adverse effects such as sedation, headache, and extrapyramidal side effects in addition to high costs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PONV is a frequent complication, and there are a lot of factors influencing it. 14,17 Many studies have shown that drugs such as metoclopramide, dexamethasone, and ondansetron can reduce PONV. Although potency of these drugs is different, they have a limited effect on PONV and they also have adverse effects such as sedation, headache, and extrapyramidal side effects in addition to high costs.…”
Section: Discussionmentioning
confidence: 99%
“…14 Studies concerning the timing of acupuncture in anesthetized patients have no clear evidence. 5,15,17 Although administering acupuncture before induction of anesthesia has been found useful in some of the studies, there are other studies that showed no difference in PONV among preoperative, intraoperative, and postoperative application of acupuncture. 15 The results of the updated Cochrane review 18 for the effectiveness of PC6 acupoint stimulation in prevention of PONV showed that there is inconclusive evidence supporting the use of a combined strategy of PC6 acupoint stimulation with antiemetic drug prophylaxis, and further, high quality trials are needed for this purpose.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence-based studies have suggested that electroacupuncture (EA) can be used to treat learning and memory impairments in rats with cerebral ischemia-reperfusion injury 26 or epilepsy 27 and to control body weight 28 and pain 29 32 . Nei Guan, also known as acupoint pericardium 6 (PC6), is the most commonly important acupressure point, especially for nausea and vomiting 33 , and can extend the time to onset of nausea, even though its function remains unknown 34 . In the present study, we hypothesized that the EA treatment would reduce the symptoms of MS through the TRPV1 pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Electroacupuncture treatment also reduces postoperative thoracic pain [ 11 ]. Studies regarding indirect stimulation of acupoints, such as the PC6 (pericardium-6: Neiguan) point stimulation band, made up of a wrist band and a bead to stimulate the acupoint, which is effective for postoperative nausea, have been published as study protocols [ 12 ], while the effectiveness of indirect acupoint-stimulating therapies to relieve postoperative pain is still unknown.…”
Section: Introductionmentioning
confidence: 99%